One-season epidemiology of injury complaints in athletics (track and field) - Edouard, P.; Dandrieux, P.-E.; Chapon, J.; Prince, C.; Charpy, S.; Bruneau, A.; Navarro, L. (Deutsche Zeitschrift für Sportmedizin, 2022)
Summary